Dinamika Likuiditas dan Risiko Green Bond vs Conventional Bond: Bukti Empiris dari Sektor Perbankan Bursa Efek Indonesia - Safitri Nurfianti; A. Ifayani Haanurat; Zalkha Soraya (Jurnal Maksipreneur, 2026)
This study examines differences in liquidity and risk between green and conventional bonds traded on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Liquidity is measured by trading volume, transaction frequency, and turnover ratio, while risk is measured by modified duration, convexity, and sensitivity. This study uses a comparative quantitative approach with purposive sampling of banking sector bonds. Data are analyzed using descriptive statistics and the Mann–Whitney test due to non-normality. Results show significant differences in trading volume, modified duration, and convexity between green and conventional bonds. However, there are no significant differences in transaction frequency, turnover ratio, and sensitivity. These findings indicate that green bonds have lower market risk and more stable prices, but still exhibit lower liquidity than conventional bonds.